Depressive Symptomatology among Norwegian Adolescent Boys and Girls: The Patient Health Questionnaire-9 (PHQ-9) Psychometric Properties and Correlates - Burdzovic Andreas, Jasmina; Brunborg, Geir S. (Frontiers in Psychology, 2017)
This study explored the potential contribution of the Diagnostic and Statistical Manual for Mental Disorders (DSM-IV) based Patient Health Questionnaire-9 item (PHQ-9) instrument to the developmental epidemiology research in Norway, by examining depressive symptoms in a school sample of adolescents (N = 846). The average PHQ-9 scores were 6.89 (SD = 5.13) for girls, and 4.57 (SD = 3.98) for boys; 8.5% of girls and 2.6% of boys were classified into the originally proposed categories indicative of Major Depressive Disorder (MDD; PHQ-9 scores > 15). Multi-group confirmatory factor analysis (CFA) confirmed a single-factor structure for the PHQ-9 with solid psychometric properties and high internal consistency for both genders. However, even though configural equality was observed, there was no evidence for metric or scalar equality across genders, warranting further investigation of measurement equivalence for the current Norwegian version of the PHQ-9. We observed no major associations between the PHQ-9 scores and adolescent religion or immigrant background. Further, school grade, not living together with both biological parents, and diagnosed chronic illness were differently associated with elevated depressive symptoms for boys and girls. Finally, high residential instability, perceived low SES, school dissatisfaction, lack of close friendships, history of suicide attempts and self-harm, and elevated emotional problems were all significantly and consistently associated with greater depression for both genders. Overall, the PHQ-9 appears to be a promising research tool, potentially offering clinically-relevant classification of adolescent self-reported depressive symptomatology in addition to the symptom severity captured by continuous scores. Nevertheless, further investigation concerning the observed measurement non-equivalence, as well as the comprehensive validation and comparison against the gold standard is required before the PHQ-9 is to be used for diagnostic screening in Norway.